"Art Girls": Philanthropy, Corporate Sponsorship, and Private Art Museums in Post‐Communist Russia. (7th October 2013) - Milam, Jennifer
Abstract Russian art sponsorship is dominated by women of the oligarch elite. Rather than dismissing this phenomenon as a faddish diversion of new money, this article takes a broader perspective on the motivations of these "art girls" along a trajectory of Russian women's involvement in patronage, philanthropy, and sponsorship extending back to the late eighteenth century. It considers how socio‐political circumstances have shaped philanthropy directed at the arts in Russia, and uses interviews to explore the reasons behind this recent focus on the contemporary in the sponsorship of exhibitions, art centers, and private museums in Moscow, St. Petersburg, and Siberia.